Activity and Predicted Nephrotoxicity of Synthetic Antibiotics Based on Polymyxin B - Gallardo-Godoy, Alejandra (J Med Chem, 2016)
[Image: see text] The polymyxin lipodecapeptides colistin and polymyxin B have become last resort therapies for infections caused by highly drug-resistant Gram-negative bacteria. Unfortunately, their utility is compromised by significant nephrotoxicity and polymyxin-resistant bacterial strains. We have conducted a systematic activity–toxicity investigation by varying eight of the nine polymyxin amino acid free side chains, preparing over 30 analogues using a novel solid-phase synthetic route. Compounds were tested against a panel of Gram-negative bacteria and counter-screened for in vitro cell toxicity. Promising compounds underwent additional testing against primary kidney cells isolated from human kidneys to better predict their nephrotoxic potential. Many of the new compounds possessed equal or better antimicrobial potency compared to polymyxin B, and some were less toxic than polymyxin B and colistin against mammalian HepG2 cells and human primary kidney cells. These initial structure–activity and structure–toxicity studies set the stage for further improvements to the polymyxin class of antibiotics.